Критические сжимающие силы и формы потери устойчивости направляющих каналов тепловыделяющих сборок ядерных реакторов ВВЭР-1000 - Ефимов, Александр Вячеславович; Максимов, М. В.; Ромашов, Юрий Владимирович (НТУ "ХПИ", 2015)
Рассмотрена устойчивость деформирования при осевом сжатии трубчатого направляющего канала, соединяющего головку и хвостовик тепловыделяющей сборки ядерного реактора ВВЭР-1000. Исследовано влияние условий закрепления краев направляющего канала на величины критических сжимающих сил и напряжений, а также на форму изгиба при потере устойчивости. Полученные величины критических сжимающих сил и напряжений показывают возможность изгиба направляющих каналов из-за потери устойчивости, причем форма такого изгиба может содержать одну-две точки перегиба, что существенно затруднит движение органов регулирования системы управления и защиты.

Consideration is given to the strain stability at axial compression of the tubular instrumentation tube guide connecting the top nozzle and the bottom nozzle of the fuel assembly of the nuclear reactor WWER-1000. The influence of the grip conditions of the edges of the instrumentation tube guide on the values of critical compressive forces and stresses and also on the shape of the bend at the stability loss has been studied. The changes in the compressive stress and force conditioned by the stochastic nature of the change in the parameters during the operation of the fuel assemblies of nuclear reactors can be comparable with the obtained relatively low critical values of 1.8 to 7.5 MPa of the compressive stress and the values of 6 to 24 kgf (kilogram-force) of the compressive force at which the bending of instrumentation tube guides is possible due to the loss of stability. Due to the insignificant minimum value and the difference between different values of the critical compressive force answering the loss of stability of the guide channel like a long compressed rod it is quite possible that the shape of the instrumentation tube guide bent due to the loss of stability during the operation will have several inflection points that will considerably hamper the motion of the regulating elements of the reactor protection and control system. Due to this fact it is reasonable to develop design diagrams that allow for the determination of critical compressive forces and axial stresses in the instrumentation tube guides taking into consideration their interaction with the top nozzle and the bottom nozzle and the spacer grid of the fuel assembly and this problem requires additional studies.
Critical compressive forces and the modes of the loss of stability in the instrumentation tube guides of the fuel assemblies of nuclear reactors ВВЭР-1000
Keywords: трубчатый направляющий канал; осевые напряжения; устойчивость деформирования; точки перегиба; fuel assembly; instrumentation tube guide; stability